2020
DOI: 10.4081/jphr.2020.1806
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Sleep Hygiene Index in Indonesian Adolescents

Abstract: Background: Sleep is associated with some behavioral factors such as maladaptive, which tend to disrupt its normal mechanism, therefore, a tool is needed to measure maladaptive sleep hygiene. This study aims to assess the psychometric properties of sleep hygiene index (SHI), translation, factor structure, validity, and reliability. Design and Methods: Data were collected from 101 Indonesia adolescents in junior high school, with SHI-Indonesia translated based on WHO guideline. The obtained data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The initial target population in the first validation of this instrument was university students (Mastin et al, 2006). However, subsequent psychometric validations in several countries have been made in the general population (Chehri et al, 2016) and specific population segments such as adolescents (Setyowatic et al, 2020), older people (Chehri et al, 2020), and patients with various diseases such as depression (Ozdemir et al, 2015) or chronic pain (Cho et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial target population in the first validation of this instrument was university students (Mastin et al, 2006). However, subsequent psychometric validations in several countries have been made in the general population (Chehri et al, 2016) and specific population segments such as adolescents (Setyowatic et al, 2020), older people (Chehri et al, 2020), and patients with various diseases such as depression (Ozdemir et al, 2015) or chronic pain (Cho et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The total score ranges from 0 to 52 points, with higher scores showing more inadequate sleep hygiene behavior. In previous validations of the SHI, the delivery mode was paper-and-pencil, although the procedure was not clear in some studies (Chehri et al, 2016(Chehri et al, , 2020Setyowatic et al, 2020). Cho et al (2013) assessed test-retest reliability using a stamped addressed envelope for a second administration, and other researchers met participants in the same setting where they had first been assessed (Mastin et al, 2006;Ozdemir et al, 2015).…”
mentioning
confidence: 99%
“…The SHI results suggest that adolescent athletes in the current study displayed better sleep behaviors than a similar aged cohort, 43 with a mean global score of 18.1. These results contrast what Setyowati et al, 43 found in 101 Indonesian adolescent school students, who scored 32 for the SHI on average. A potential reason for the difference in results observed between the two studies could be the differing school times, with a 7am start and 1pm finish in Indonesia, compared with approximately 8:40am and 3:20pm in New Zealand.…”
Section: Discussionmentioning
confidence: 55%
“…42 Additionally, results from the ESS suggest that adolescent athletes have normal amounts of daytime sleepiness (mean global score of 8.5). The SHI results suggest that adolescent athletes in the current study displayed better sleep behaviors than a similar aged cohort, 43 with a mean global score of 18.1. These results contrast what Setyowati et al, 43 found in 101 Indonesian adolescent school students, who scored 32 for the SHI on average.…”
Section: Ttb (H:min)mentioning
confidence: 55%
See 1 more Smart Citation